Use of amazonian shrimp (Macrobrachium amazonicum) waste for the elaboration of flavoring and dried soup (Research, Society and Development, 2024)
The objective of the study was to use the Amazonian shrimp (Macrobrachium amazonicum) processing residues for the elaboration of a flavoring agent and dehydrated soups. The shrimp were captured on Ilha Tabatinga-PA, frozen at -18ºC and transported to UFMA/Campus Pinheiro -MA, where they were thawed, peeled, weighed, washed and the residues cooked in a pressure cooker and subsequently dried in an oven, crushed and sieved. Two soup formulations were prepared with different percentages of the flavoring agent, F1 (40%) and F2 (30%). Centesimal composition, microbiological and sensory analysis were carried out. The results were submitted to analysis of variance (ANOVA), and when significant differences were detected, the Tukey test was performed at a 5% significance level. Moisture was lower in flavoring (5.98%) compared to soups, F1 (7.29%) and F2 (7.01%), crude protein (71.25%) and lipids (10.05%) in flavoring were higher than those found in soups F1 (57.73%, 4.20%) and F2 (62.36%, 3.58%) respectively. Mineral matter was higher in flavoring (23.86%) compared to soups, F1 (19.68%) and F2 (19.68%). Microbiological analysis showed that the flavoring and soups were within the standards required by law. In the sensory analysis, both formulations showed good acceptance and F2 was the favorite, where the evaluators would eat often or always. The use of shrimp waste to make soups is an alternative to encourage the full use of shrimp waste, without discarding it into the environment.